Evaluasi kondisi permukaan jalan metode pavement condition indeks dalam meningkatkan keselamatan pada Ruas Penghubung Weleri-Sukorejo - Hasna Aulia Rahma; Riza Phahlevi Marwanto; Yogi Oktopianto (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
Road surface degradation poses significant risks to service quality and traffic safety, necessitating systematic evaluation for effective rehabilitation. This study assessed the condition of the Weleri-Sukorejo road segment using the Pavement Condition Index (PCI) method and safety inspections to formulate targeted rehabilitation strategies. The 12 km road was divided into six segments for visual surveys, with PCI calculations following ASTM D6433 guidelines. Results revealed PCI values ranging from 28 (very poor) to 99 (excellent), averaging 64.5 (fair). Critical findings identified severe damage in segments 0+000–2+000 (PCI 35) and 2+100–4+000 (PCI 28), dominated by potholes (29%) and polished aggregate (24%), requiring immediate structural intervention. Moderate degradation in segments 10+100–12+000 (PCI 64) and 4+100–6+000 (PCI 72) highlighted the need for periodic maintenance, while high-PCI segments (6+100–10+000) warranted routine upkeep. Key contributing factors included overloading, substandard materials, and inadequate drainage. Recommendations prioritize structural rehabilitation, material standardization, and preventive maintenance to enhance road safety and longevity. The study contributes by providing a technical evaluation approach based on PCI data to support more accurate, measurable, and safety-oriented road rehabilitation planning on national road segments.